2020
DOI: 10.1002/adma.202004053
|View full text |Cite
|
Sign up to set email alerts
|

Mutually Reinforced Polymer–Graphene Bilayer Membranes for Energy‐Efficient Acoustic Transduction

Abstract: Graphene holds promise for thin, ultralightweight, and high‐performance nanoelectromechanical transducers. However, graphene‐only devices are limited in size due to fatigue and fracture of suspended graphene membranes. Here, a lightweight, flexible, transparent, and conductive bilayer composite of polyetherimide and single‐layer graphene is prepared and suspended on the centimeter scale with an unprecedentedly high aspect ratio of 105. The coupling of the two components leads to mutual reinforcement and create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…For example, single-layer graphene was suspended over a lightweight, flexible, transparent, and conductive bilayer composite of polyetherimide to create an energy-efficient, high-performance nanoelectromechanical transducer [ 27 ]. Graphene membranes have also been used to make a graphene varactor, allowing its capacitance to be finely tuned using voltage-induced deflection [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, single-layer graphene was suspended over a lightweight, flexible, transparent, and conductive bilayer composite of polyetherimide to create an energy-efficient, high-performance nanoelectromechanical transducer [ 27 ]. Graphene membranes have also been used to make a graphene varactor, allowing its capacitance to be finely tuned using voltage-induced deflection [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low mass, good mechanical properties, high electrical and thermal conductivity have made graphene‐based materials such as CVD graphene and reduced graphene oxide interesting materials for different types of acoustic transducers including electrostatic (ESL) [ 5,6 ] and thermoacoustic loudspeakers. [ 7 ] Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…The fragility of multilayer graphene is a concern for long‐term durability. More recently, Khan et al [ 6 ] reported a mechanically robust ESL with a diaphragm comprising a single layer graphene atop a polyetherimide membrane. The diaphragm has shown promise for low power consumption and SPL in the mid‐ to high‐ frequency range (>500 Hz) comparable to commercial microspeakers.…”
Section: Introductionmentioning
confidence: 99%
“…Screening is also tied to a material’s conductivity, which, together with polarizability, is a key performance element for graphene-based bio- and chemical sensors . Recent progress in the preparation of polymer-containing graphene devices includes doping by ultrathin polymer layers , and fabrication of free-standing polymer-supported graphene membranes . A combination of such strategies, as described here, allowed for more direct probing of the graphene–polymer interface for the first time without perturbation associated with the thickness of the organic layer.…”
mentioning
confidence: 99%
“…43 Recent progress in the preparation of polymercontaining graphene devices includes doping by ultrathin polymer layers 24,26 and fabrication of free-standing polymersupported graphene membranes. 44 A combination of such strategies, as described here, allowed for more direct probing of the graphene−polymer interface for the first time without perturbation associated with the thickness of the organic layer. Previous observations have shown that overlayer thickness has a complex impact on surface electronic measurements, 26 and thus minimizing this influence is of great interest.…”
mentioning
confidence: 99%